2021
DOI: 10.1007/s00268-020-05887-3
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Mesh in Surgery: A Comprehensive Review and Meta‐Analysis of Selected Outcomes in 51 Studies and 6079 Patients

Abstract: Background In recent decades, biologic mesh (BM) has become an important adjunct to surgical practice. Recent evidence‐based clinical applications of BM include but are not limited to: reconstruction of abdominal wall defects; breast reconstruction; face, head and neck surgery; periodontal surgery; other hernia repairs (diaphragmatic, hiatal/paraesophageal, inguinal and perineal); hand surgery; and shoulder arthroplasty. Prior systematic reviews of BM in complex abdominal wall hernia repair had several shortco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 136 publications
(470 reference statements)
1
5
0
Order By: Relevance
“…Sensitivity analyses performed to assess heterogeneity have shown that patient characteristics are not a source of this heterogeneity. Similar results are reported in the review by Samson et al [ 45 ]. This review included studies using biological implants in open VHR and analyzed reporting data on early complications, late complications, and recurrences.…”
Section: Discussionsupporting
confidence: 92%
“…Sensitivity analyses performed to assess heterogeneity have shown that patient characteristics are not a source of this heterogeneity. Similar results are reported in the review by Samson et al [ 45 ]. This review included studies using biological implants in open VHR and analyzed reporting data on early complications, late complications, and recurrences.…”
Section: Discussionsupporting
confidence: 92%
“…Once the chatbots were trained, we asked that it generate a scientific abstract based on the information provided. For each of the 10 abstracts, the chatbots were given the introduction and discussion of 3 relevant publications . Text limitations prevented us from giving the chatbots the entire article.…”
Section: Methodsmentioning
confidence: 99%
“…Early data suggests that non cross-linked biological meshes entail less fistula recurrence risk compared to cross-linked meshes [65,66 ▪ ]. Bridging placement of biological mesh poses a higher risk of hernia recurrence [67 ▪ ]. Nevertheless, avoidance of fistula recurrence should be prioritized over hernia development in these patients.…”
Section: Abdominal Wall Closure or Reconstructionmentioning
confidence: 99%